The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ccr3.5124
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense variant in MED12 associated with malformations in a female fetus

Abstract: Pathogenic variants in the MED12 gene located on the X‐chromosome have primarily been reported in males with Lujan‐Fryns syndrome, Ohdo syndrome and the Opits‐Kaveggia syndrome. However, earlier reports of female patients and female mice suggest that MED12 deficiency causes severe malformations. We report a novel example of a MED12 de novo nonsense variant in a female fetus with severe malformations identified by trio‐exome sequencing. This finding further expands the clinical spectrum of MED12‐related disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…[1][2][3] To our knowledge, this is the second case in which HS was diagnosed in utero. Faergeman et al 4 Many studies have reported that the adoption of a systematic examination including a standardized protocol can achieve a significant increase in the detection rate of anomalies in early gestation. 5,6 Detailed assessment of fetal anatomy is necessary at least in highrisk pregnancies such as those with increased NT, as evidenced by our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] To our knowledge, this is the second case in which HS was diagnosed in utero. Faergeman et al 4 Many studies have reported that the adoption of a systematic examination including a standardized protocol can achieve a significant increase in the detection rate of anomalies in early gestation. 5,6 Detailed assessment of fetal anatomy is necessary at least in highrisk pregnancies such as those with increased NT, as evidenced by our case.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the second case in which HS was diagnosed in utero. Faergeman et al 4 . reported the prenatal diagnosis of a MED12 de novo nonsense variant c.6196 C > T, p.(Gln2066*) in a female fetus identified by exome sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…However, known clues to MED12 deficiency by prenatal tests are scarce. By prenatal sonography, agenesis of the corpus callosum (ACC) ( Jiang et al, 2019 ), cleft lip and cleft palate ( Faergeman et al, 2021 ), microphthalmia ( Amodeo et al, 2020 ; Faergeman et al, 2021 ), microretrognathia ( Amodeo et al, 2020 ), heart disease ( Amodeo et al, 2020 ; Faergeman et al, 2021 ), broad thumbs and halluces ( Kato et al, 1994 ; Graham et al, 1999 ), and fetal digital pads ( Clark et al, 2009 ) have been reported in fetal MED12 deficiency; in terms of phenotype, congenital clinodactyly and overriding toes were documented in some of postnatal patients with XLOS ( Patil et al, 2017 ), which indicates possible prenatal ultrasound findings. In the oldest patient in this study, the postnatal findings of hallux rigidus and congenital heart disease (CHD) prompt a diagnosis of MED12 deficiency, although the patient failed to receive a comprehensive genetic test.…”
Section: Discussionmentioning
confidence: 99%